2018
DOI: 10.1093/jas/sky435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marbling and enhancement’s abilities to compensate for reduced beef palatability at elevated degrees of doneness1

Abstract: The objectives of this study were to evaluate the extent marbling compensates for reduced beef palatability at elevated degrees of doneness and to determine the relationship of residual moisture and fat in cooked steaks to beef palatability, specifically beef juiciness. Paired strip loins (IMPS # 180) were collected to equally represent five quality treatments [Prime, Top Choice (modest and moderate marbling), Low Choice, Select, and Select Enhanced (110% of raw weight)]. Steaks were grouped into sets of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
39
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 33 publications
8
39
3
Order By: Relevance
“…This compensation for decreased palatability that marbling provides is commonly known as the "insurance theory" (Smith and Carpenter, 1974;Savell and Cross, 1988). To date, only 1 study has thoroughly evaluated the interaction between marbling and DOD in depth through sensory evaluation (Drey et al, 2019). In our study, no quality grade × DOD interactions were present in all consumer sensory rating data.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…This compensation for decreased palatability that marbling provides is commonly known as the "insurance theory" (Smith and Carpenter, 1974;Savell and Cross, 1988). To date, only 1 study has thoroughly evaluated the interaction between marbling and DOD in depth through sensory evaluation (Drey et al, 2019). In our study, no quality grade × DOD interactions were present in all consumer sensory rating data.…”
Section: Discussionmentioning
confidence: 68%
“…Previous literature has established that as DOD increases, tenderness, juiciness, flavor, and overall acceptability of steaks decrease linearly (Parrish et al, 1973;Akinwunmi et al, 1993;O'Quinn et al, 2018). More notably, recent studies have demonstrated enhancement and higher degrees of marbling can compensate for detrimental effects on palatability that are associated with increasing DOD in the LL (Lucherk et al, 2016;Drey et al, 2019). This compensation for decreased palatability that marbling provides is commonly known as the "insurance theory" (Smith and Carpenter, 1974;Savell and Cross, 1988).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… Huff-Lonergan et al (2002) established marbling was correlated to both subjective and objective pork palatability measures. Drey et al (2019) demonstrated the effect marbling has on improved consumer and trained panel tenderness, juiciness, and flavor ratings. Juarez et al (2011) found pork chops from barrows were 1.2 points greater in flavor than gilts.…”
Section: Discussionmentioning
confidence: 99%